Fireproof alumina nanofiber and preparation method thereof

By introducing Zn2+ into the electrospinning method, refractory alumina nanofibers were prepared, which solved the problem of poor thermal insulation effect of conventional methods at high temperatures, and achieved higher thermal conductivity and better high-temperature thermal insulation effect.

CN119710983APending Publication Date: 2025-03-28YAAN BESTRY PERFORMANCE MATERIALS CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411874890.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The alumina nanofibers prepared by conventional electrospinning method are still poor in thermal insulation at high temperatures.

Method used

Zn2+ is introduced into the precursor solution for electrospinning. The preparation method includes mixing a soluble aluminum source and a soluble zinc source with a mixed solvent, stirring to prepare a mixed solution A, adding a spun aid agent to prepare a precursor solution B, electrospinning and insulating calcining to obtain refractory alumina nanofibers.

Benefits of technology

The obtained refractory alumina nanofiber has a thermal conductivity of 0.25~0.40W/m·k at 800°C, and has better high-temperature heat insulation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710983A_ABST
    Figure CN119710983A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a fire-resistant alumina nanofiber, and belongs to the technical field of alumina. The method comprises the following steps: mixing a soluble aluminum source and a soluble zinc source with a mixed solvent, and stirring to prepare a mixed solution A; adding a spinning aid and stirring to prepare a precursor solution B; performing electrostatic spinning on the precursor solution B to obtain precursor fibers; and carrying out heat-preservation calcination on the precursor fiber to obtain the alumina nanofiber. The average fiber diameter of the refractory alumina nanofiber is 0.2-0.3 [mu] m, and the thermal conductivity of the refractory alumina nanofiber is 0.25-0.40 W / m.k at the temperature of 800 DEG C measured by a laser thermal conductivity instrument. In order to solve the problem that an aluminum oxide nanofiber crystal prepared by a conventional electrostatic spinning method is still poor in heat insulation effect at high temperature, the invention provides a fireproof aluminum oxide nanofiber and a preparation method thereof. The finally prepared refractory alumina nanofiber has a better high-temperature heat insulation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alumina, and in particular to a refractory alumina nanofiber and a preparation method thereof. Background Art

[0002] Al2O3 fiber has the advantages of light weight, high temperature resistance, small thermal expansion coefficient, good thermal shock resistance, etc. It can be used in special equipment such as high efficiency and energy saving, military, aerospace, etc., which are not met by traditional thermal insulation materials. At the same time, Al2O3 fiber also has excellent infrared heating effect and thermal radiation capacity, so it can be used as lining material for high-temperature furnaces such as ceramic firing kilns, petrochemical cracking furnaces, and combustion furnaces.

[0003] For example, the Chinese invention application (title: "A method for preparing alumina nanofibers using electrospinning", publication number: CN113151933A, publication date: 20210723) discloses that aluminum salt, high molecular organic matter, pure water and alcohol are configured into a driving solution, and then mixed fibers are obtained by electrospinning technology, and finally alumina nanofibers are obtained by high-temperature sintering.

[0004] However, the thermal insulation effect of alumina nanofibers prepared by conventional electrospinning is still poor at high temperatures. Summary of the invention

[0005] The present invention solves the problem that the thermal insulation effect of aluminum oxide nanofibers prepared by conventional electrospinning is still poor at high temperatures, and provides a refractory aluminum oxide nanofiber and a preparation method thereof. 2+ , so that the thermal conductivity of the final refractory alumina nanofibers is 0.25~0.40W / m·k at 800℃, which has better high-temperature thermal insulation effect.

[0006] The technical solution adopted by the present invention is: A method for preparing refractory alumina nanofibers comprises the following steps: Step S1, mixing a soluble aluminum source and a soluble zinc source with 10 mL of a mixed solvent, and stirring to form a mixed solution A; wherein the molar concentration of Al3+ in the soluble aluminum source in the mixed solution A is 0.2-0.5 mol / L, and the molar proportion of Zn2+ in the soluble zinc source is 0.5-2% of the Al3+ in the soluble aluminum source; and the mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2; Step S2, adding 0.8-1.5 g of a spinning aid into the mixed solution A, and stirring to prepare a precursor solution B; Step S3, transferring the precursor solution B into a syringe, and performing electrospinning under preset conditions to obtain precursor fibers; Step S4, calcining the precursor fiber at a high temperature to obtain alumina nanofibers.

[0007] Furthermore, when preparing the mixed solution A in step S1, the stirring time is 1 to 12 hours.

[0008] Furthermore, the soluble aluminum source is one or more of aluminum chloride, aluminum nitrate, sodium aluminate, aluminum isopropoxide, and aluminum sulfate.

[0009] Furthermore, the soluble zinc source is one or more of zinc chloride, zinc nitrate, zinc sulfate, zinc carbonate, zinc phosphate, and zinc acetate.

[0010] Furthermore, when the precursor solution B is prepared in step S2, the heating temperature is 50-80° C. and the stirring time is 1-48 hours.

[0011] Furthermore, the spinning aid is one or more of polyvinyl butyral, polyvinyl alcohol, and polyvinyl pyrrolidone; wherein the relative molecular mass of the polyvinyl butyral is 90,000 to 120,000, the relative molecular mass of the polyvinyl alcohol is 75,000 to 100,000, and the average molecular mass of the polyvinyl pyrrolidone is 1,300,000.

[0012] Furthermore, the preset conditions are: mechanical pump injection speed 0.3~1mL / h, the distance between the spinning needle and the receiving roller is 5~20cm, the roller receiver speed is 100~2500rpm, the spinning voltage is 10~20kV, the ambient temperature is 20~30℃, and the ambient relative humidity is ≤40%.

[0013] Furthermore, in the step S4, the alumina nanofibers are calcined at a temperature of 950-1050° C. for a holding time of 1-5 hours.

[0014] Furthermore, when the alumina nanofibers are calcined at a temperature of 2-10°C / min in step S4.

[0015] Based on the same inventive concept, the present invention also provides a refractory alumina nanofiber, the elemental composition of the fiber contains Zn, the average fiber diameter is 0.2-0.3 μm, and the thermal conductivity measured by a laser thermal conductivity meter at 800°C is 0.25-0.40 W / m·k.

[0016] The beneficial effects of the present invention are: The present invention provides a refractory alumina nanofiber and a preparation method thereof, wherein Zn is introduced into a precursor solution B for electrospinning. 2+ , so that the thermal conductivity of the final refractory alumina nanofibers is 0.25~0.40W / m·k at 800℃, which has better high-temperature thermal insulation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 The present invention is a schematic diagram of the preparation process of the refractory alumina nanofibers.

[0019] Figure 2 This is a scanning electron microscope image of the aluminum oxide nanofibers in Example 1. DETAILED DESCRIPTION

[0020] The embodiments of the invention are described in detail below with reference to the accompanying drawings.

[0021] A method for preparing refractory alumina nanofibers, the process of which is as follows Figure 1 As shown in , the method comprises the following steps: Step S1, mixing a soluble aluminum source and a soluble zinc source with 10 mL of a mixed solvent, and stirring to prepare a mixed solution A; wherein the Al in the soluble aluminum source in the mixed solution A is 3+ The molar concentration of Zn in the soluble zinc source is 0.2-0.5 mol / L. 2+ The molar proportion of Al in the soluble aluminum source is 3+ 0.5-2%; the mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2; Step S2, adding 0.8-1.5 g of a spinning aid into the mixed solution A, and stirring to prepare a precursor solution B; Step S3, transferring the precursor solution B into a syringe, and performing electrospinning under preset conditions to obtain precursor fibers; Step S4, calcining the precursor fiber at a high temperature to obtain alumina nanofibers.

[0022] Furthermore, when preparing the mixed solution A in step S1, the stirring time is 1 to 12 hours.

[0023] Furthermore, the soluble aluminum source is one or more of aluminum chloride, aluminum nitrate, sodium aluminate, aluminum isopropoxide, and aluminum sulfate. The soluble zinc source is one or more of zinc chloride, zinc nitrate, zinc sulfate, zinc carbonate, zinc phosphate, and zinc acetate.

[0024] Furthermore, when the precursor solution B is prepared in step S2, the heating temperature is 50-80° C. and the stirring time is 1-48 hours.

[0025] Furthermore, the spinning aid is one or more of polyvinyl butyral, polyvinyl alcohol, and polyvinyl pyrrolidone; wherein the relative molecular mass of the polyvinyl butyral is 90,000 to 120,000, the relative molecular mass of the polyvinyl alcohol is 75,000 to 100,000, and the average molecular mass of the polyvinyl pyrrolidone is 1,300,000.

[0026] Furthermore, the preset conditions are: mechanical pump injection speed 0.3~1mL / h, the distance between the spinning needle and the receiving roller is 5~20cm, the roller receiver speed is 100~2500rpm, the spinning voltage is 10~20kV, the ambient temperature is 20~30℃, and the ambient relative humidity is ≤40%.

[0027] Furthermore, in step S4, the alumina nanofibers are calcined at a temperature of 950-1050° C. for 1-5 hours. In step S4, the alumina nanofibers are calcined at a heating rate of 2-10° C. / min.

[0028] The following is an explanation using a more specific example.

[0029] Example 1

[0030] A method for preparing refractory alumina nanofibers comprises the following steps: (1) Weigh an appropriate amount of aluminum nitrate and dissolve it in 10 mL of mixed solvent, then add an appropriate amount of zinc nitrate (molar ratio of Zn 2+ :Al 3+ =0.5:100), stirred at room temperature for 2 hours, and configured to A1 3+ A mixed solution A with a molar concentration of 0.2 mol / L. The mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2.

[0031] (2) Add 0.8 g of polyvinyl alcohol (PVA) (molecular weight 80,000) to the mixed solution A, and stir on a magnetic stirring heating table at 75 °C for 24 h to obtain a precursor sol B.

[0032] (3) Electrospinning was performed under preset conditions for 10 h to obtain precursor fibers; wherein the preset conditions were: a mechanical pump injection rate of 0.3 mL / h, a distance between the spinning needle and the receiving roller of 10 cm, a roller receiver speed of 800 rpm, a spinning voltage of 15 kV, an ambient temperature of 25 °C, and an ambient relative humidity of 40%.

[0033] (4) The precursor fiber was placed in a muffle furnace, and then heated to 1000°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain alumina nanofibers. The scanning electron microscopy observation results of the alumina nanofibers are shown in FIG. Figure 2 As shown in , its average diameter is 0.2 μm; at the same time, the laser thermal conductivity tester measures its thermal conductivity at 800°C to be 0.370 W / m·k.

[0034] Example 2

[0035] A method for preparing refractory alumina nanofibers comprises the following steps: (1) Weigh an appropriate amount of aluminum nitrate and dissolve it in 10 mL of mixed solvent, then add an appropriate amount of zinc nitrate (molar ratio of Zn 2+ :Al 3+ =1:100), stirred at room temperature for 2 hours, and prepared into A1 3+ A mixed solution A with a molar concentration of 0.2 mol / L. The mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2.

[0036] (2) Add 0.8 g of polyvinyl alcohol (PVA) (molecular weight 80,000) to the mixed solution A, and stir on a magnetic stirring heating table at 75 °C for 24 h to obtain a precursor sol B.

[0037] (3) Electrospinning was performed under preset conditions for 10 h to obtain precursor fibers; wherein the preset conditions were: a mechanical pump injection rate of 0.3 mL / h, a distance between the spinning needle and the receiving roller of 10 cm, a roller receiver speed of 800 rpm, a spinning voltage of 15 kV, an ambient temperature of 25 °C, and an ambient relative humidity of 40%.

[0038] (4) The precursor fiber was placed in a muffle furnace, and then heated to 1000°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain alumina nanofibers. The average diameter of the alumina nanofibers was 0.2 μm; at the same time, the thermal conductivity at 800°C was measured by a laser thermal conductivity tester to be 0.341 W / m·k.

[0039] Example 3

[0040] A method for preparing refractory alumina nanofibers comprises the following steps: (1) Weigh an appropriate amount of aluminum nitrate and dissolve it in 10 mL of mixed solvent, then add an appropriate amount of zinc nitrate (molar ratio of Zn 2+ :Al 3+ =2:100), stirred at room temperature for 2 hours, and prepared into A1 3+ A mixed solution A with a molar concentration of 0.2 mol / L. The mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2.

[0041] (2) Add 0.8 g of polyvinyl alcohol (PVA) (molecular weight 80,000) to the mixed solution A, and stir on a magnetic stirring heating table at 75 °C for 24 h to obtain a precursor sol B.

[0042] (3) Electrospinning was performed under preset conditions for 10 h to obtain precursor fibers; wherein the preset conditions were: a mechanical pump injection rate of 0.3 mL / h, a distance between the spinning needle and the receiving roller of 10 cm, a roller receiver speed of 800 rpm, a spinning voltage of 15 kV, an ambient temperature of 25 °C, and an ambient relative humidity of 40%.

[0043] (4) The precursor fiber was placed in a muffle furnace, and then heated to 1000°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain alumina nanofibers. The average diameter of the alumina nanofibers was 0.2 μm; at the same time, the thermal conductivity at 800°C was measured by a laser thermal conductivity tester to be 0.369 W / m·k.

[0044] Example 4

[0045] A method for preparing refractory alumina nanofibers comprises the following steps: (1) Weigh an appropriate amount of aluminum nitrate and dissolve it in 10 mL of mixed solvent, then add an appropriate amount of zinc nitrate (molar ratio of Zn 2+ :Al 3+ =1:100), stirred at room temperature for 2 hours, and prepared into A1 3+ A mixed solution A with a molar concentration of 0.5 mol / L. The mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2.

[0046] (2) Add 1.5 g of polyvinyl alcohol (PVA) (molecular weight 80,000) to the mixed solution A, and stir on a magnetic stirring heating table at 75 °C for 24 h to obtain a precursor sol B.

[0047] (3) Electrospinning was performed under preset conditions for 10 h to obtain precursor fibers; wherein the preset conditions were: a mechanical pump injection rate of 0.3 mL / h, a distance between the spinning needle and the receiving roller of 10 cm, a roller receiver speed of 800 rpm, a spinning voltage of 15 kV, an ambient temperature of 25 °C, and an ambient relative humidity of 40%.

[0048] (4) The precursor fiber was placed in a muffle furnace, and then heated to 1000°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain alumina nanofibers. The average diameter of the alumina nanofibers was 0.3 μm; at the same time, the thermal conductivity at 800°C was measured by a laser thermal conductivity tester to be 0.287 W / m·k.

[0049] Example 5

[0050] A method for preparing refractory alumina nanofibers comprises the following steps: (1) Weigh an appropriate amount of aluminum nitrate and dissolve it in 10 mL of mixed solvent, then add an appropriate amount of zinc nitrate (molar ratio of Zn 2+ :Al 3+ =1:100), stirred at room temperature for 2 hours, and prepared into A1 3+ A mixed solution A with a molar concentration of 0.4 mol / L. The mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2.

[0051] (2) Add 0.8 g of polyvinyl alcohol (PVA) (molecular weight 80,000) to the mixed solution A, and stir on a magnetic stirring heating table at 75 °C for 24 h to obtain a precursor sol B.

[0052] (3) Electrospinning was performed under preset conditions for 10 h to obtain precursor fibers; wherein the preset conditions were: a mechanical pump injection rate of 0.3 mL / h, a distance between the spinning needle and the receiving roller of 10 cm, a roller receiver speed of 800 rpm, a spinning voltage of 15 kV, an ambient temperature of 25 °C, and an ambient relative humidity of 40%.

[0053] (4) The precursor fiber was placed in a muffle furnace, and then heated to 1000°C at a heating rate of 5°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain alumina nanofibers. The average diameter of the alumina nanofibers was 0.3 μm; at the same time, the thermal conductivity at 800°C was measured by a laser thermal conductivity tester to be 0.317 W / m·k.

[0054] Comparative Example 1 A method for preparing refractory alumina nanofibers comprises the following steps: (1) Weigh an appropriate amount of aluminum nitrate and dissolve it in 10 mL of mixed solvent. Stir at room temperature for 2 hours to prepare A1 3+ A mixed solution A with a molar concentration of 0.2 mol / L. The mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2.

[0055] (2) Add 0.8 g of polyvinyl alcohol (PVA) (molecular weight 80,000) to the mixed solution A, and stir on a magnetic stirring heating table at 75 °C for 24 h to obtain a precursor sol B.

[0056] (3) Electrospinning was performed under preset conditions for 10 h to obtain precursor fibers; wherein the preset conditions were: a mechanical pump injection rate of 0.3 mL / h, a distance between the spinning needle and the receiving roller of 10 cm, a roller receiver speed of 100 rpm, a spinning voltage of 15 kV, an ambient temperature of 25 °C, and an ambient relative humidity of 40%.

[0057] (4) The precursor fiber was placed in a muffle furnace, and then heated to 1000°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain alumina nanofibers. The average diameter of the alumina nanofibers was 0.3 μm; at the same time, the thermal conductivity at 800°C was measured by a laser thermal conductivity tester to be 0.521 W / m·k.

[0058] Comparative Example 2 A method for preparing refractory alumina nanofibers comprises the following steps: (1) Weigh an appropriate amount of aluminum nitrate and dissolve it in 10 mL of mixed solvent. Stir at room temperature for 2 hours to prepare A1 3+ A mixed solution A with a molar concentration of 0.2 mol / L. The mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2.

[0059] (2) Add 1.2 g of polyvinyl alcohol (PVA) (molecular weight 80,000) to the mixed solution A, and stir on a magnetic stirring heating table at 75 °C for 24 h to obtain a precursor sol B.

[0060] (3) Electrospinning was performed under preset conditions for 10 h to obtain precursor fibers; wherein the preset conditions were: a mechanical pump injection rate of 0.3 mL / h, a distance between the spinning needle and the receiving roller of 10 cm, a roller receiver speed of 800 rpm, a spinning voltage of 15 kV, an ambient temperature of 25 °C, and an ambient relative humidity of 40%.

[0061] (4) The precursor fiber was placed in a muffle furnace, and then heated to 1000°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain alumina nanofibers. The average diameter of the alumina nanofibers was 0.3 μm; at the same time, the thermal conductivity at 800°C was measured by a laser thermal conductivity tester to be 0.553 W / m·k.

[0062] Comparative Example 3 A method for preparing refractory alumina nanofibers comprises the following steps: (1) Weigh an appropriate amount of aluminum nitrate and dissolve it in 10 mL of mixed solvent. Stir at room temperature for 2 hours to prepare A1 3+ A mixed solution A with a molar concentration of 0.5 mol / L. The mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2.

[0063] (2) Add 1.5 g of polyvinyl alcohol (PVA) (molecular weight 80,000) to the mixed solution A, and stir on a magnetic stirring heating table at 75 °C for 24 h to obtain a precursor sol B.

[0064] (3) Electrospinning was performed under preset conditions for 10 h to obtain precursor fibers; wherein the preset conditions were: a mechanical pump injection rate of 0.3 mL / h, a distance between the spinning needle and the receiving roller of 10 cm, a roller receiver speed of 800 rpm, a spinning voltage of 15 kV, an ambient temperature of 25 °C, and an ambient relative humidity of 40%.

[0065] (4) The precursor fiber was placed in a muffle furnace, and then heated to 1000°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain alumina nanofibers. The average diameter of the alumina nanofibers was 0.33 μm; at the same time, the thermal conductivity at 800°C was measured by a laser thermal conductivity tester to be 0.562 W / m·k.

[0066] Comparative Example 4 A method for preparing refractory alumina nanofibers comprises the following steps: (1) Weigh an appropriate amount of aluminum nitrate and dissolve it in 10 mL of mixed solvent, then add an appropriate amount of zinc nitrate (molar ratio of Zn 2+ :Al 3+ =5:100), stirred at room temperature for 2 hours, and prepared into A1 3+ A mixed solution A with a molar concentration of 0.5 mol / L. The mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2.

[0067] (2) Add 1.2 g of polyvinyl alcohol (PVA) (molecular weight 80,000) to the mixed solution A, and stir on a magnetic stirring heating table at 75 °C for 24 h to obtain a precursor sol B.

[0068] (3) Electrospinning was performed under preset conditions for 10 h to obtain precursor fibers; wherein the preset conditions were: a mechanical pump injection rate of 0.3 mL / h, a distance between the spinning needle and the receiving roller of 10 cm, a roller receiver speed of 800 rpm, a spinning voltage of 15 kV, an ambient temperature of 25 °C, and an ambient relative humidity of 40%.

[0069] (4) The precursor fiber was placed in a muffle furnace, and then heated to 1000°C at a heating rate of 5°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain alumina nanofibers. The average diameter of the alumina nanofibers was 0.3 μm; at the same time, the thermal conductivity at 800°C was measured by a laser thermal conductivity tester to be 0.453 W / m·k.

[0070] Comparative Example 5 A method for preparing refractory alumina nanofibers comprises the following steps: (1) Weigh an appropriate amount of aluminum nitrate and dissolve it in 10 mL of mixed solvent, then add an appropriate amount of zinc nitrate (molar ratio of Zn 2+ :Al 3+=10:100), stirred at room temperature for 2 hours, and prepared into A1 3+ A mixed solution A with a molar concentration of 0.5 mol / L. The mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2.

[0071] (2) Add 1.5 g of polyvinyl alcohol (PVA) (molecular weight 80,000) to the mixed solution A, and stir on a magnetic stirring heating table at 75 °C for 24 h to obtain a precursor sol B.

[0072] (3) Electrospinning was performed under preset conditions for 10 h to obtain precursor fibers; wherein the preset conditions were: a mechanical pump injection rate of 0.3 mL / h, a distance between the spinning needle and the receiving roller of 10 cm, a roller receiver speed of 800 rpm, a spinning voltage of 15 kV, an ambient temperature of 25 °C, and an ambient relative humidity of 40%.

[0073] (4) The precursor fiber was placed in a muffle furnace, and then heated to 1000°C at a heating rate of 5°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain alumina nanofibers. The average diameter of the alumina nanofibers was 0.32 μm; at the same time, the thermal conductivity at 800°C was measured by a laser thermal conductivity tester to be 0.437 W / m·k.

[0074] The preparation process conditions of Examples 1 to 5 and Comparative Examples 1 to 5 and the test results of the prepared alumina nanofibers are summarized in Table 1.

[0075] Table 1 Preparation process conditions and test results

[0076] Table 1-1 Preparation process conditions and test results

Claims

1. A method for preparing refractory alumina nanofibers, characterized in that: The following steps are involved: Step S1, mixing a soluble aluminum source and a soluble zinc source with 10 mL of a mixed solvent, and stirring to prepare a mixed solution A; wherein the Al in the soluble aluminum source in the mixed solution A is 3+ The molar concentration of Zn in the soluble zinc source is 0.2-0.5 mol / L. 2+ The molar proportion of Al in the soluble aluminum source is 3+ 0.5-2%; the mixed solvent is composed of pure water and ethanol in a volume ratio of 3:2; Step S2, adding 0.8-1.5 g of a spinning aid into the mixed solution A, and stirring to prepare a precursor solution B; Step S3, transferring the precursor solution B into a syringe, and performing electrospinning under preset conditions to obtain precursor fibers; Step S4, calcining the precursor fiber at a high temperature to obtain alumina nanofibers.

2. The method for preparing refractory alumina nanofibers according to claim 1, characterized in that: When preparing the mixed solution A in step S1, the stirring time is 1 to 12 hours.

3. The method for preparing refractory alumina nanofibers according to claim 1 or 2, characterized in that: The soluble aluminum source is one or more of aluminum chloride, aluminum nitrate, sodium aluminate, aluminum isopropoxide, and aluminum sulfate.

4. The method for preparing refractory alumina nanofibers according to claim 1 or 2, characterized in that: The soluble zinc source is one or more of zinc chloride, zinc nitrate, zinc sulfate, zinc carbonate, zinc phosphate and zinc acetate.

5. The method for preparing refractory alumina nanofibers according to claim 1, characterized in that: When the precursor solution B is prepared in step S2, the heating temperature is 50-80° C. and the stirring time is 1-48 hours.

6. The method for preparing refractory alumina nanofibers according to claim 1 or 5, characterized in that: The spinning aid is one or more of polyvinyl butyral, polyvinyl alcohol and polyvinyl pyrrolidone; wherein the relative molecular mass of the polyvinyl butyral is 90,000 to 120,000, the relative molecular mass of the polyvinyl alcohol is 75,000 to 100,000, and the average molecular mass of the polyvinyl pyrrolidone is 1,300,000.

7. The method for preparing refractory alumina nanofibers according to claim 1, characterized in that: The preset conditions are: mechanical pump injection speed 0.3-1 mL / h, distance between spinning needle and receiving roller 5-20 cm, roller receiver speed 100-2500 rpm, spinning voltage 10-20 kV, ambient temperature 20-30° C., ambient relative humidity ≤40%.

8. The method for preparing refractory alumina nanofibers according to claim 1, characterized in that: When the alumina nanofibers are calcined in step S4, the temperature is 950-1050° C. and the insulation time is 1-5 hours.

9. The method for preparing refractory alumina nanofibers according to claim 1 or 8, characterized in that: When the alumina nanofibers are calcined at a temperature of 2-10°C / min in step S4.

10. A refractory alumina nanofiber, characterized in that: The element composition of the fiber contains Zn, the average fiber diameter is 0.2-0.3 μm, and the thermal conductivity is 0.25-0.40 W / m·k at 800°C as measured by a laser thermal conductivity meter.

Citation Information

Patent Citations

  • Method for preparing alumina nanofiber by electrostatic spinning

    CN113151933A